Successful anti-IL-6 treatment for interstitial lung disease associated with STAT3 gain-of-function: a case report and literature review - Zhou, Peng; Zhu, Meifang; Pan, Yuting; Jin, Jing; Fan, Zhidan; Yu, Haiguo (Frontiers in Pediatrics, 2025)
Autosomal dominant gain-of-function (GOF) variants in the signal transducer and activator of transcription 3 (STAT3) result in an inborn error of immunity characterized by multi-organ autoimmunity and lymphoproliferation. In this study, we retrospectively analyzed a rare case of STAT3 GOF mutation with thrombocytopenia, immunoglobulin deficiency, and recurrent respiratory infections. Whole-exome sequencing revealed a heterozygous mutation (c. 2144C > T, p. P715l) in the STAT3 gene. The patient initially received only anti-infective and immunoglobulin-supportive therapies at an external hospital, which proved unsatisfactory. Over time, the patient developed severe interstitial lung disease (ILD) and arthritis, which were effectively managed with tocilizumab at our hospital. This case underscores the importance of early diagnosis and timely initiation of biological therapy for the management of ILD with STAT3 GOF mutations.